The Hong Kong-China Government's Democratic Instability in terms of the Political Realism Perspective - I.G.A.AG Dewi Sucitawathi P (JED (Jurnal Etika Demokrasi), 2020)
Abstract. The political stability and governance of a country are greatly influenced by public support and the commitment of public officials to accommodate the people's voice. The chaos that occurred in mainland China from June 2019 until the end of 2020 became a reflection that the political system of government of 'One Country, Two Systems' was a formidable challenge for the Chinese government after the surrender of Hong Kong by the British on July 1, 1997, where China used the communism system and on the other hand, Hong Kong uses a system of liberalism. Hong Kong's strong understanding of freedom makes this region very sensitive on several issues, one of which is legal issues due to the killing of Hong Kong citizens in the country of Taiwan. This article aims to explain the dualism of leadership used by the Hong Kong-China government, which led to anarchism, political instability of the government, and causing the investment climate in Hong Kong-China to decline sharply. The research method used is a qualitative method, with secondary data types taken from journals, book literature, and official websites used to search for theories and data that are vaild. This research shows that political realism in the demonstration case in Hong Kong is proof that the state in this case the central government in Beijing still has the power to always interfere in Hong Kong's domestic affairs.Keywords: Democratic Instability, Political Realism, One Country Two SystemsAbstrak.  Stabilitas politik dan pemerintahan sebuah negara sangat dipengaruhi dukungan masyarakat dan komitmen pejabat publik untuk mengakomodir suara rakyat. Kekacauan yang terjadi di daratan China sejak bulan Juni 2019  hingga akhir tahun 2020 menjadi cerminan bahwa sistem politik pemerintahan ‘Satu Negara, Dua Sistem’ merupakan tantangan berat bagi pemerintah China pasca diserahkannya Hongkong oleh Inggris pada 1 Juli 1997, dimana China menggunakan sistem komunisme, dan dipihak lain Hongkong menggunakan sistem liberalisme. Kuatnya pemahaman Hongkong terhadap kebebasan menyebabkan wilayah ini sangat sensitif dalam beberapa isu, salah satunya isu hukum akibat adanya peristiwa pembunuhan yang dilakukan warga Hongkong di negara Taiwan. Artikel ini bertujuan untuk menjelaskan dualisme kepemimpinan yang digunakan pemerintah Hongkong-China, yang berujung pada peristiwa anarkisme, instabilitas politik pemerintahan, hingga menyebabkan iklim investasi di Hongkong-China merosot tajam. Metode penelitian yang digunakan metode kualitatif, dengan jenis data sekunder diambil dari jurnal, literatur buku, dan website resmi yang digunakan untuk mencari teori dan data yang vaild. Penelitian ini menunjukkan bahwa realisme politik dalam kasus demonstrasi di Hongkong menjadi bukti bahwa negara dalam hal ini pemerintah pusat di Beijing tetap memiliki kekuasaan untuk selalu ikut campur tangan terhadap urusan dalam negeri HongkongKata Kunci: Instabilitas Demokrasi, Realisme Politik, Satu Negara Dua Sistem